Taiping theology: the localization of Christianity in China, 1843-64 - Kilcourse, Carl S. (Christianities of the world, 2016)
1. Introduction -- 2. Missions and localization in Chinese history -- 3. The Taiping vision of world salvation -- 4. The heavenly father and his non-divine sons -- 5. A Confucianized Christian ethic -- 6. Sacrifice and charisma in the heavenly kingdom -- 7. Poetry and patriarchy in the heavenly palace